RASIONALITAS PENGHAPUSAN UJIAN NASIONAL TERHADAP SEMANGAT BELAJAR PADA SISWA SMPN 3 ACEH BARAT - Devi Intan Chadijah; Lilis Sariyanti; Yeni Srilestari (Jurnal Society : Pengamat Perubahan Sosial, 2022)
The policy of abolishing national exams has been running for 2 years, but still has pros and cons in society. On the one hand, the abolition of national exams is considered to be able to stimulate the talents possessed by each student in depth. However, on the other hand, abolition of national exams has affected students' low enthusiasm for learning. The aim of this research is to describe students' enthusiasm for learning since the implementation of the abolition national exams. The method used is descriptive qualitative with purposive sampling. The research results revealed that the impact of the policy of abolishing national exams was proven to have reduced enthusiasm for learning which was influenced by the rational choices of each student. Students have enthusiasm for learning when there is urgency, coercion or high fear, such as during national exams. There are changes to learning methods that unconsciously make students feel confused and choose not to be active in studying. The loss of intervention from parents is due to the lack of urgency that requires students to continue studying actively. The reduction in the number of outstanding students is the impact of the decline in enthusiasm for learning among students